2015
DOI: 10.33584/jnzg.2015.77.475
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of chicory, plantain, red clover and white clover in a sward mix for increased sheep and beef production

Abstract: Many farmers are sowing mixed swards containing chicory (Cichorium intybus), plantain (Plantago lanceolata), red clover (Trifolium pratense) and white clover (T. repens) (hereafter termed herb and clover mix). This herb and clover mix has comparable annual dry matter (DM) production to perennial ryegrass white clover pasture (rye/wc), however, it has a different pattern of growth, producing more DM during summer and autumn. The herb and clover mix also has a higher nutritive value and is able to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 27 publications
0
41
2
Order By: Relevance
“…Previous authors have reported differences in herbage nutritive composition between herb/clover mixtures and perennial ryegrass and white clover swards (Golding et al., ; Hutton et al., ; Somasiri et al., ). The herb/clover mixtures had lower fibre content, similar CP content, higher OMD and metabolizable energy content than the PRG and white clover mixtures in those studies (Cranston, Kenyon, Morris, & Kemp, ). However, the likely nutritional benefit of herb and clover inclusion in the sward was partially diluted by the presence of grass in the swards in the current study compared with the swards reported by the aforementioned authors.…”
Section: Discussionmentioning
confidence: 61%
“…Previous authors have reported differences in herbage nutritive composition between herb/clover mixtures and perennial ryegrass and white clover swards (Golding et al., ; Hutton et al., ; Somasiri et al., ). The herb/clover mixtures had lower fibre content, similar CP content, higher OMD and metabolizable energy content than the PRG and white clover mixtures in those studies (Cranston, Kenyon, Morris, & Kemp, ). However, the likely nutritional benefit of herb and clover inclusion in the sward was partially diluted by the presence of grass in the swards in the current study compared with the swards reported by the aforementioned authors.…”
Section: Discussionmentioning
confidence: 61%
“…The paddocks were strip grazed every 6-8 weeks throughout summer/autumn and again in spring, by either dairy cows or by calves ( Table 2). The paddocks were not grazed during winter (June to August), as per best practice grazing management recommendations for plantain-dominant swards (Ayala et al, 2011a;Cranston et al, 2015a). The paddocks were grazed when the pre-grazing sward height reached a minimum of 25 cm, down to a 7 cm post-grazing residual (~1800 kgDM/ha).…”
Section: Grazing and Pesticide Managementmentioning
confidence: 99%
“…Grazing management was not altered in the current study to facilitate the natural reseeding of plan-tain. However, given that the paddocks were not grazed during winter, or grazed below 7 cm, as per best management practice for plantain dominant swards (Ayala et al, 2011a;Cranston et al, 2015a), this may have been beneficial to the survival of seedlings. Regardless, the success of natural reseeding in this study suggests that no change in spring or summer management is needed to enable successful plantain seedling recruitment.…”
Section: Paddockmentioning
confidence: 99%
See 1 more Smart Citation
“…These herb and clover species as monocultures or as mixtures are utilised in temperate climates in North America (Sanderson et al, 2005;Lombardi et al, 2015), Australasia (Reed et al, 2008;Raeside et al, 2014;Pembleton et al, 2016) and in Europe (Marley et al, 2003;Andersen et al, 2009) for sheep and cattle production. Recently, it has been reported that herb clover mixtures containing plantain, chicory, white and red clovers can improve lamb live weight gain and carcass weights in spring, summer and autumn (Golding et al, 2011;Cranston et al, 2015;Somasiri et al, 2015a,b;Somasiri et al, 2016a,b). These studies however were season specific while the forages utilised are perennial species and therefore productivity on both an annual and multiple year basis is of interest to farmers.…”
Section: Introductionmentioning
confidence: 99%